2022
DOI: 10.1007/s13355-021-00766-2
|View full text |Cite
|
Sign up to set email alerts
|

Pollination efficiency of bumblebee, honeybee, and hawkmoth in kabocha squash, Cucurbita maxima, production in Kagoshima, Japan

Abstract: Kabocha squash, Cucurbita maxima Duchesne, in delayed-start culture is one of the major cultivation systems in southwestern Japan. Honeybee introduction or hand-pollination has been practiced in this crop system, but the species composition, abundance, and pollination efficiency of major pollinators remain unclear. In the current study, we investigated which insect(s) accomplish pollination of kabocha squash. Among the total visitations to female flowers, honeybees, mostly Apis mellifera L. (Hymenoptera: Apida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(42 reference statements)
0
7
1
Order By: Relevance
“…This result supported our preliminary survey of C. maxima conducted in the same sites and season from 2017 to 2018 (Ikemoto unpublished data and Ikemoto et al, 2021). Although the previous study carried out at the same site of Kagoshima in autumn 2019 and 2020 (Kamo et al, 2022) reported B. d. diversus visiting C. maxima, we did not find any individuals in this study. Such an inconsistent result between the two studies could simply be because the experimental periods in our study were earlier than the appearance season of the workers (Kinota et al, 2013).…”
Section: Geographic Variations Of Pollinators and Reproductive Succes...contrasting
confidence: 92%
See 1 more Smart Citation
“…This result supported our preliminary survey of C. maxima conducted in the same sites and season from 2017 to 2018 (Ikemoto unpublished data and Ikemoto et al, 2021). Although the previous study carried out at the same site of Kagoshima in autumn 2019 and 2020 (Kamo et al, 2022) reported B. d. diversus visiting C. maxima, we did not find any individuals in this study. Such an inconsistent result between the two studies could simply be because the experimental periods in our study were earlier than the appearance season of the workers (Kinota et al, 2013).…”
Section: Geographic Variations Of Pollinators and Reproductive Succes...contrasting
confidence: 92%
“…pollinate, or at least visit the flowers (Ali et al., 2014; Hoehn et al., 2008; Pfister et al., 2017). On the other hand, in Japan, elucidation of pollinator importance of each insect for squashes is scarce, except for a few studies conducted in northern (Hokkaido) and southern (Kagoshima in Kyushu) areas (Abe & Kumano, 2017; Kamo et al., 2022). In other words, we still lack information for Honshu, the main island of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study on Cucurbita maxima , bumblebees carried considerably more pollen on their bodies than honeybees (Kamo et al, 2022). Due to their pollen transport capacity and behavior within the flower, bumblebees also effectively deposited more pollen than honeybees or other floral visitors (Kamo et al, 2022). Honeybee, Apis mellifera , is a non‐native farmed insect in Finland.…”
Section: Discussionmentioning
confidence: 92%
“…Insect morphology imposes selective pressure on flowers to match the reproductive displays of the sexes. In a previous study on Cucurbita maxima, bumblebees carried considerably more pollen on their bodies than honeybees (Kamo et al, 2022). Due to their pollen transport capacity and behavior within the flower, bumblebees also effectively deposited more pollen than honeybees or other floral visitors (Kamo et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…However, flower visits by wild pollinators may fluctuate over time [ 17 ], and there may be multiple important pollinators whose relative importance may change over the years. Although several studies have investigated the relative importance of multiple pollinators over time [ 6 , 18 , 19 ], few have investigated their fluctuations over multiple years [ 6 , 20 , 21 ]. Moreover, no studies have estimated the proportional importance of each major flower visitor to the total pollination service of the field crops.…”
Section: Introductionmentioning
confidence: 99%